Development of an online clinical trial recruitment portal for the NIHR mental health BRC. Issue 1 (December 2016) - Markham, Sarah
Plain English summary In order to test whether or not new treatments for mental health disorders help patients get better according to clinician/patient selected criteria, it is often necessary to test them on patients under safe, carefully monitored conditions called clinical trials. It is necessary to find enough patients to take part in a clinical trial so that the results of the trial are reliable. The NIHR Mental Health BRC (here after abbreviated to BRC) is a centre for research in London which seeks to find out better ways to treat patients with mental health difficulties. The BRC has experienced problems trying to find sufficient numbers of patients to participate in its clinical trials as it appears that insufficient patients were being told by their doctor about opportunities to participate in clinical research. In order to help the BRC find enough patients to volunteer to take part in its clinical trials, the author (a patient representative) of this article and a clinical researcher in the nearby Institute of Psychiatry, Psychology and Neuroscience (IoPPN) decided to work together to try to find the best way to let patients know more about what clinical trials are, what it is like to take part in them and which clinical trials are seeking patients to take part. The author and researcher used a report by the Association of Medical Research Charities (AMRC) on patient difficulties in finding clinical trials to take part in, and the recommendations it made, to guide them in building a website to give such patients the information on clinical trials they wanted (including clinical trials run by the BRC). The author and researcher also asked patients, carers, staff at the IoPPN and BRC what they thought of the website and how to make it better. They used the ideas, suggestions and criticisms to improve the website. The author and researcher also asked mental health charities and research organisations if they would advertise the final version of this website on their own websites; many said yes, they would. The manager of the BRC on reviewing the website, agreed that a final version of the website with the NIHR Mental Health BRC logo would be paid for and will form part of a new main website for the BRC in early 2016. Abstract ᅟ ᅟ Public & patient recruitment to clinical trials is viewed as one of the main barriers to the implementation of clinical trials. This difficulty is often attributed to the working culture of the NHS, rapid turnover of staff and patients and poor-gatekeeping in referring patients to suitable clinical trials. In response to the recruitment difficulties experienced by the Psychosis Studies Clinical Academic Group at the NIHR Mental Health Biomedical Research Centre, Denmark Hill, London, a member of the Office of Psychosis Studies at King's College London and a member (the author) of the King's Clinical Trials Unit, King's College London developed an initiative to create an online clinical trial recruitment portal/information hub for the NIHR Mental Health BRC. The primary purpose of this initiative being to promote patient and public awareness of and interest in participating in clinical trials.